Manajemen Pembelajaran Daring dalam Kegiatan Pesantren Virtual di Kabupaten Banyumas - Kuswantoro Kuswantoro (Assosiation of Islamic Education Lecturer of Universitas Jenderal Soedirman, 2021)
The COVID-19 pandemic causes all educational and learning activities to be delivered in online, incuding the Islamic teaching in Ramadan 2021 activities. This research emphasizes the aspects of planning, implementating, and evaluating the implementation of virtual pesantren carried out by Kelompok Kerja Guru Pendidikan Agama Islam (KKG PAI) for Elementary Schools in Banyumas regency. The research is qualitative research. The primary data has been collected from the teachers, the students and the parents of the elementary schools students in Banyumas regency. The data has been collected by observation, interviews, and documentations. The pesantren Ramadan delivered virtually through the social media sites such as YouTube channel by Hestek team. The teacher has recorded a talk as the learning material and uploaded to the social media. The student have to record their activities during pesantren Ramadan that will be evaluated by the teacher. This virtual pesantren Ramadan is effective to improve Islamic religious knowledge of the students.